Atlas of cancer of the skin (Churchill Livingston, 2000)
Univ. Hospital of Zurich, Switzerland. Provides an overview of the most frequent and important tumors of the skin by describing their typical morphologic features and describing the most important facts. Includes information on diagnostic tools and therapeutic approaches. High-quality color illustrations. For clinicians and researchers.